Isozyme analysis for characterization of Ganoderma strains from south‐east Asia - Miller, R. N. G.; Holderness, M.; Bridge, P. D.; Paterson, R. R. M.; Hussin, M. Z.; Meon, Sariah (Wiley, 1995)
Extracellular pectinase isozymes were determined by polyacrylamide gel electrophoresis (PAGE) for isolates of Ganoderma collected from a range of hosts and environments in south‐east Asia. Findings indicate these techniques to be of use in the differentiation of strains isolated from different hosts and environments. Average linkage cluster analysis of pectinase isozyme banding patterns separated isolates according to host of origin.